Exploration of Hiptage (Malpighiaceae) diversity in Vietnam reveals a new species with wingless fruits - Mai Thi Xuan Lam; Marie-Stella Jagou; Giang Quoc Van; Florent Martos; Truc Thi Ngoc Nguyen; Truong Van Do; Rafael Felipe de Almeida; Hoa Dang Tran; Khoa Dang Tran; Giang Thi Nguyen; Dong Phuong Tran; Ky Huynh; et al. (PhytoKeys)
Hiptage (Malpighiaceae) is a genus almost exclusively native to Asia, with a single species, Hiptage benghalensis, being a noxious invasive plant in several areas of the world and particularly threatening the native flora of the Mascarene Islands. Whereas 17 Hiptage species have been reported from Vietnam, there is currently no available genetic information that could be used to confirm the species diversity in the country. Through a study combining phylogenetic and morphological analyses of newly-collected samples and herbarium specimens, we were able to accurately identify five Hiptage species in Vietnam. One of these, Hiptage aptera, represents a species new to science. Specimens of the new species show white to slightly pink petals, erect to forward-curved petals, eight tiny calyx glands and wingless fruits, a unique feature within this genus. Our results strongly support Vietnam as one of the diversity centres of the Hiptage genus with 18 species out of the 48 species. Although we could not determine the source of introduction of Hiptage in the Mascarenes Archipelago, our findings highlight the genetic similarity of all Hiptage benghalensis samples collected in its secondary distribution areas, suggesting a probable single introduction. This is consistent with historical reports dating the plant’s introduction to the Mascarenes to the 18th century.